(untitled) (Al-Nahrain Journal of Science, 2018)
Adsorption isotherms of some phenolics from aqueous solutions onto activated carbon were studied in the concentration range (0.030 to 2.083) mmol.dm-3 at 25 C. The pH of the solutions ranged from 6.5 to 6.8 . The adsorption data were correlated well with the Langmuir adsorption isotherm in the range of concentrations studied. The effect of the introduction of NH2 , CH3 , Cl , and NO2 groups to phenol molecule, the effect of substituted position in cresols and aminophenols, and the effect of the number of substituted NO2 groups in nitrophenols on adsorption were investigated. Electrostatic interaction and hydrogen bonding between the carbon surface and the solute molecules is postulated to explain the adsorption data.